Catalytic asymmetric Meerwein–Ponndorf–Verley reduction of glyoxylates induced by a chiral N, N′-dioxide/Y(OTf)3 complex. Issue 22 (3rd March 2017) - Wu, Wangbin; Zou, Sijia; Lin, Lili; Ji, Jie; Zhang, Yuheng; Ma, Baiwei; Liu, Xiaohua; Feng, Xiaoming
Abstract : An asymmetric MPV reduction of glyoxylates was for the first time achieved with excellent results and the mechanism of the reaction was probed. Abstract : An asymmetric Meerwein–Ponndorf–Verley (MPV) reduction of glyoxylates was for the first time accomplished via an N, N ′-dioxide/Y(OTf)3 complex with aluminium alkoxide and molecular sieves (MSs) as crucial additives. A variety of optically active α-hydroxyesters were obtained with excellent results. A possible reaction mechanism was proposed based on the experiments.